The Effect of Facility Security Classification on Serious Rules Violation Reports in California Prisons: A Regression Discontinuity Design - Tahamont, Sarah (Journal of quantitative criminology, 2019)
Prison facility security classification is intended to recognize differences across inmates with regard to the propensity to commit misconduct and to appropriately house inmates with varying levels of violent and/or antisocial behavior while they are incarcerated. The intent of security classification is to increase safety for staff and other inmates, but little is known about the effect of security classification on prison misconduct.